ONCE MORE ABOUT PHAGE THERAPY: WHAT IS RIGHT, AND WHAT IS NOT - V. M. Popova; E. L. Zhilenkov; A. Y. Zurabov (Медицинский совет, 2016)
A little more than 100 years ago the article “An investigation on the nature of ultra-microscopic viruses” by the English physician and researcher F. Twort was published in The Lancet. Twort described the phenomenon of transparent spots which occurred on the bacterial lawn when he worked with bacterial cultures using a petri dish. He examined the spots and found zones of dead bacteria. The spots were transmissible: they appeared on other dishes once transferred to a new lawn. Twort, failing to give a convincing explanation for this phenomenon, proposed three hypotheses:  it could be an unusual manifestation of the bacterial life cycle, or an enzyme produced by the bacteria themselves or some sort of “ultra-microscopic virus” which could cause the death of bacteria. Having voiced his hypotheses, Tvort let the matter drop, but many believe that with the article began the era of bacteriophages.